Therapeutic Efficacy and Safety of Paeoniae Radix Rubra Formulae in Relieving Hyperbilirubinemia Induced by Viral Hepatitis: A Meta-Analysis - Huang, Yin-Qiu; Ma, Xiao; Wang, Jian; Zhao, Yan-Ling; Wang, Jia-Bo; Chen, Zhe; Zhu, Yun; Shan, Li-Mei; Wei, Shi-Zhang; Wang, Ji; Xiao, Xiao-He (Frontiers in Pharmacology, 2016)
Objective: Hyperbilirubinemia is one of the most devastating pathologies induced by various liver diseases. Formulae related to Paeoniae Radix Rubra (PRR) at high doses have been applied to treat hyperbilirubinemia in traditional Chinese medicine. The aim of this systematic review and meta-analysis is to assess the efficacy and safety of formulae relevant to high-dose PRR in patients suffering from hyperbilirubinemia induced by viral hepatitis. Methods: We performed a meta-analysis of randomized-controlled clinical trials to evaluate the efficacy and safety of formulae that apply a high dose of PRR for hyperbilirubinemia. Seven databases were searched until April 2015. All studies were included according to detailed criteria and assessed for methodological quality. The outcome measurements were recorded for further analysis using the Revman 5.2.11 software. Results: Fifteen articles involving 1323 patients with hyperbilirubinemia were included. Formulae with high-dose PRR might promote the efficacy of either a combined application ([OR: 3.98, 95%CI (2.91, 5.43)]; P<0.01) or a single application ([OR: 4.00, 95%CI (1.50, 10.68)]; P<0.01) for hyperbilirubinemia. The indices of TBIL, ALT and AST significantly decreased ([MD: -75.57, 95%CI (-94.88, -56.26)], [MD: -26.54, 95%CI (-36.19, -16.88)] and ([MD: -28.94, 95%CI (-46.26, -11.61)]; P<0.01), respectively. In addition, formulae with high-dose PRR could enhance the treatment efficacy of hyperbilirubinemia triggered by hepatitis B ([OR: 2.98, 95% CI (1.75, 5.05)]; P<0.01). Furthermore, the efficacy was enhanced with an increasing dosage of PRR. Two articles reported that no side effects occurred in clinical trials, and 3 studies noted that patients presented light digestive tract symptoms. Conclusion: Formulae relevant to high-dose PRR ameliorate hyperbilirubinemia and might constitute a promising therapeutic approach. For widespread acceptance by practitioners, more rigorously designed multicenter, double-blind, randomized and large-scale controlled trials are required.